Analisis Kasus Penistaan Agama dalam Perspektif Forum Umat Islam Sumatera Utara - Irwansyah, Rio; Fitriani, Fitriani (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2025)
This study discusses the response of the Forum of Islamic Community of North Sumatra Amal Ma’ruf Nahi Munkar (FUI-SU AMANAR) to the case of religious blasphemy committed by RS in Medan Sunggal. This study aims to analyze the form of religious blasphemy committed and the response given by FUI-SU AMANAR, as well as to seek solutions to the problem. The method used is qualitative descriptive with a phenomenological approach to religion. The results show that the RS case provoked emotional and collective responses from the community, including mass actions and demands for law enforcement officials to take action. FUI-SU AMANAR took concrete steps by conducting clarifications, internal investigations, and mediation with authorities. This research emphasizes that religious blasphemy in the digital era has wide social impacts that spread rapidly, thus requiring wise, firm, and peaceful responses from various parties, especially religious organizations. The study also provides understanding about the importance of Islamic organizations in maintaining social harmony and acting as a balancing force in the religious dynamics of society.